2004
DOI: 10.1108/14684520410531682
|View full text |Cite
|
Sign up to set email alerts
|

Managerial implications of computer‐based online/face‐to‐face business education: a case study

Abstract: Online business education is becoming increasingly common in tertiary education in response to the growing needs of a changing student population. E‐learning and teaching online business have unique challenges when compared to their more traditional classroom counterparts, which promotes the concepts of a nimble organisation from the managers’ perspective. A recent survey of 35 students at a major private university in Pittsburgh, Pennsylvania, who were chosen based on recent successful participation within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Unless someone deliberately reveals personal information, participants have no idea about the age, gender, ethnic background, or physical characteristics of others online. Similar conclusions regarding the reduction of discrimination and prejudice about on-line learning is also given by Smith and Rupp (2004). The discussions that ensue are about as free of socio-cultural bias as possible.…”
Section: Student Demographic Backgroundsupporting
confidence: 59%
See 3 more Smart Citations
“…Unless someone deliberately reveals personal information, participants have no idea about the age, gender, ethnic background, or physical characteristics of others online. Similar conclusions regarding the reduction of discrimination and prejudice about on-line learning is also given by Smith and Rupp (2004). The discussions that ensue are about as free of socio-cultural bias as possible.…”
Section: Student Demographic Backgroundsupporting
confidence: 59%
“…The descriptive summary of the respondents is listed in Table 1. One thing worth mentioning is that our sample's overall descriptive profile is similar to the profile of a sample that was used for on-line learning study and reported by eCollege.com and Smith and Rupp (2004).…”
Section: Purpose Of the Study And Its Survey Proceduresmentioning
confidence: 79%
See 2 more Smart Citations
“…It is less expensive and faster to deliver, promotes independent learning, provides good accessibility from anywhere and any time, and gives students more control over their learning processes (Cantoni et al, 2004;Dewhurst and Williams, 1998;Smith and Rupp, 2004). According to the 2004 "Teachers Talk Tech" survey conducted by CDW Government, Inc., a leading provider of technology to governments and educators in the USA, 81 percent of teachers reported that information technology in education increases students' academic performance.…”
Section: Introductionmentioning
confidence: 99%